Iraq Crude Oil Exports – July, August, September/ 2024 - SOMO, Oil Marketing Company (Journal of Petroleum Research and Studies, 2025)
Table 1. Iraq Crude Oil Exports – July 2024 Table 2. Iraq Crude Oil Exports – August 2024 Table 3. Iraq Crude Oil Exports – September 2024